Screening of SERT and p11 mRNA Levels in Airline Pilots: A Translational Approach - Becerril-Villanueva, Enrique; Olvera-Alvarez, María Irma; Alvarez-Herrera, Samantha; Maldonado-García, Jose Luis; López-Torres, Adolfo; Ramírez-Marroquín, Oscar Abelardo; González-Ruiz, Octavio; Nogueira-Fernández, José Manuel; Mendoza-Contreras, José Manuel; Sánchez-García, Héctor Omar; José-Alfallo, José Antonio; Valencia Baños, Atenodoro; et al. (Frontiers in Psychiatry, 2022)
Airline pilots are frequently exposed to numerous flights per week, changes in their circadian rhythms, and extended periods away from home. All these stressors make pilots susceptible to developing psychiatric disorders. Recently, emphasis has been placed on the need for molecular tests that help in the diagnosis of depression. The genes SLC6A4 and S100A10 encode serotonin transporter (SERT) and p11 protein, respectively. Their expression has been frequently associated with stress and depression. In this work, we quantified, by quantitative PCR, the expression of SERT and p11 in peripheral mononuclear cells of airline pilots compared to patients with depression and healthy volunteers. Moreover, by mass spectrometry, we quantified the serum serotonin levels in the same three groups. We found that SERT and p11 were overexpressed in the mononuclear cells of airline pilots and depressed patients compared to healthy volunteers. Although serum serotonin was not different between healthy volunteers and airline pilots, a decreasing trend was observed in the latter. As expected, serum serotonin in the patients was significantly lower. Alterations in SERT and p11 in airline pilots could be related to professional stress, a condition that could potentially affect their long-term mental health.